The Anatomy and Morphology of the Superficial Peroneal Nerve - Ribak, Samuel; Fonseca, Juliano R.; Tietzmann, Alexandre; Gama, Sérgio A. M.; Hirata, Helton H. (Journal of Reconstructive Microsurgery, 2016)
Background Knowledge on the anatomical and morphological characteristics of the superficial peroneal nerve is amenable to further refinement. This cadaveric study aimed to further evaluate anatomical and morphological characteristics of the superficial peroneal nerve.Methods In this study, 10 lower limbs from five fresh cadavers were dissected. The anatomical characteristics of the superficial peroneal nerve were identified. Nerve segments were submitted for histological and morphometric analyses, and nerve thicknesses and number of fascicles were assessed.Results Regarding the superficial peroneal nerve's bifurcation, 80% of the terminal branches were distal to the point of emergence from the fascia. In 90% limbs, two sensory branches were observed immediately after the distal bifurcation of the superficial peroneal nerve. The mean distance from the fibular head to the superficial peroneal nerve's emergence from the fascia was 24.6 cm and mean nerve thickness at this point was 0.3 cm. The mean distance between the lateral malleolus and the main nerve trunk at the ankle was 4.68 cm. The mean distance from the motor branch of the peroneus brevis to the lateral malleolus was 29.3 cm. Morphometric analyses revealed an average five nerve bundles at the broadest nerve diameter (2.6 mm).Conclusion The anatomical and morphometrical characteristics of the superficial peroneal nerve indicate that it may be a safe and useful donor for autologous graft treatment of peripheral nerve injuries. Our morphological study shows a median of five fascicles, and that the thickest diameter of the nerve was 2.6 mm at the emergence from the deep to the superficial compartment.
Keywords: nerve graft; superficial peroneal nerve; anatomic variations; surgical anatomy